2021
DOI: 10.3389/fphar.2021.722530
|View full text |Cite
|
Sign up to set email alerts
|

Huangqi Shengmai Yin Ameliorates Myocardial Fibrosis by Activating Sirtuin3 and Inhibiting TGF-β/Smad Pathway

Abstract: Myocardial fibrosis (MF) is an important pathological process in which a variety of cardiovascular diseases transform into heart failure. The main manifestation of MF is the excessive deposition of collagen in the myocardium. Here, we explored whether Huangqi Shengmai Yin (HSY) can inhibit isoprenaline (ISO)-induced myocardial collagen deposition in rats, thereby reducing the cardiac dysfunction caused by MF. The results of echocardiography showed that HSY upregulated fractional shortening and ejection fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In a mouse model of angiotensin II (Ang-II)-induced cardiac fibrosis, SIRT3-KO mice developed more serious cardiac fibrosis than WT controls, while the overexpression of SIRT3 by lentivirus transfection partly reversed these results. Further studies demonstrated that SIRT3 directly binds to and deacetylates signal transducer and activator of transcription 3 (STAT3) to inhibit its activity, which leads to reduced expression of nuclear factor of activated T cells 2 (NFATc2), the downstream factor of STAT3 [ 174 ]. In addition, SIRT3 KO accelerated pericyte-myofibroblast/fibroblast transition, promoted Ang-II-induced NADPH oxidase-derived ROS formation and increased the expression of TGF-β1, indicating new mechanisms by which SIRT3 protects against Ang-II-induced cardiac fibrosis [ 175 ].…”
Section: Mitochondrial Sirtuins In Fibrosismentioning
confidence: 99%
“…In a mouse model of angiotensin II (Ang-II)-induced cardiac fibrosis, SIRT3-KO mice developed more serious cardiac fibrosis than WT controls, while the overexpression of SIRT3 by lentivirus transfection partly reversed these results. Further studies demonstrated that SIRT3 directly binds to and deacetylates signal transducer and activator of transcription 3 (STAT3) to inhibit its activity, which leads to reduced expression of nuclear factor of activated T cells 2 (NFATc2), the downstream factor of STAT3 [ 174 ]. In addition, SIRT3 KO accelerated pericyte-myofibroblast/fibroblast transition, promoted Ang-II-induced NADPH oxidase-derived ROS formation and increased the expression of TGF-β1, indicating new mechanisms by which SIRT3 protects against Ang-II-induced cardiac fibrosis [ 175 ].…”
Section: Mitochondrial Sirtuins In Fibrosismentioning
confidence: 99%